Grandaustralis, a new genus and Grandaustralis boomerang, a new species of Cetoniinae (Coleoptera: Scarabaeidae) from Western Australia - Hutchinson, Paul M.; Moeseneder, Christian H. (Zootaxa, 2013)
Grandaustralis new genus and Grandaustralis boomerang new species are described from Western Australia. Grandaus-tralis is placed in the tribe Schizorhinini (Coleoptera: Scarabaeidae: Cetoniinae).